Beyond Juvenile Delinquency: Youth Involvement as Perpetrators of Criminality - Henky Fernando; Irwan Abdullah; Yuniar Galuh Larasati; Riky Novarizal; Leanne Morin (Universitas Andalas, 2024)
Adolescents' involvement as perpetrators of criminality in Indonesia has gone beyond the patterns of deviant behavior and actions categorized as juvenile delinquency. Adolescents' involvement as perpetrators of criminality has not been given much scientific attention in previous studies. This study focuses on the question,